(NaMMONITIDY KELLOWEJSKIH OTLOVENIJ sEWERNOGO kAWKAZA (B:s (Ns (B4 (NTABLICAMI (B/s - (N~IHA^EW(B, (NpAWEL kONSTANTINOWI^s ((NlENINGRAD (B;s (NmOSKWA (B;s (NnOWOSIBIRSK (B:s (NgOS(B. (NNAU^(B.-(NTEHN(B. (NGORNO(B-(NGEOL(B.-(NNEFT(B. (NIZD(B-(NWO(B,s, 1933)
(NrEZ@ME NA ANGL(B. (NQZ(B.s
Keywords: (NaMMONITIDYs -- (NpALEONTOLOGIQs -- (NsEWERNYJ kAWKAZs